2011
DOI: 10.1371/journal.pone.0024358
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate Liposomes Improve Metabolic Profile and Reduce Visceral Adipose Macrophage Content in Diet-Induced Obese Mice

Abstract: BackgroundObesity-related adipose inflammation has been thought to be a causal factor for the development of insulin resistance and type 2 diabetes. Infiltrated macrophages in adipose tissue of obese animals and humans are an important source for inflammatory cytokines. Clodronate liposomes can ablate macrophages by inducing apoptosis. In this study, we aim to determine whether peritoneal injection of clodronate liposomes has any beneficial effect on systemic glucose homeostasis/insulin sensitivity and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 45 publications
4
103
1
Order By: Relevance
“…4G, 4H). To confirm the role of macrophages in the expansion of Tregs in vivo, we depleted macrophages in miR-155 ASO-treated ALI mice using clodronate liposomes as reported previously (43). Data showed that compared with the control group, the proliferation of Tregs in the clodronate liposome-treated group decreased significantly on day 4 ( Fig.…”
Section: Macrophages Dominantly Induced the Proliferation Of Tregssupporting
confidence: 58%
“…4G, 4H). To confirm the role of macrophages in the expansion of Tregs in vivo, we depleted macrophages in miR-155 ASO-treated ALI mice using clodronate liposomes as reported previously (43). Data showed that compared with the control group, the proliferation of Tregs in the clodronate liposome-treated group decreased significantly on day 4 ( Fig.…”
Section: Macrophages Dominantly Induced the Proliferation Of Tregssupporting
confidence: 58%
“…In fact, TNFα administration is used to induce insulin resistance in mice, and insulin sensitivity can be restored both by pharmacological inhibition of TNFα and reversal of the M2 M1 switch, 7 supporting the damaging role of macrophages and distinguishing them as a target for clinical intervention. [10][11][12] Importantly, visceral adipose tissue (VAT, surrounding the organs) is thought to be the primary site of these pathological effects, as opposed to subcutaneous adipose tissue (beneath the skin). 13 Most clinical treatments for obesity comorbidities, such as insulin or statins, act downstream of inflammatory processes rather than resolving the underlying causes.…”
mentioning
confidence: 99%
“…Recent data further strengthen the link between Kupffer cell activation after high-fat feeding, NASH and the development of hepatic insulin resistance [66,67]. The role of activated Kupffer cells on hepatic insulin sensitivity was assessed by depleting Kupffer cells using liposome-encapsulated clodronate in C57BL/6J mice fed a high-fat diet.…”
Section: Kupffer Cells Link Lipid Metabolism and Inflammationmentioning
confidence: 89%